Perancangan Interior Vihara Buddhayana Surabaya - Aprilia Pratama (Intra, 2017)
Vihara is a symbol of Buddhism. The various streams that make the monastery one with the other have the emphasis of its own teaching derived from the history and the value of Buddhahood. Design object that being used is Buddhayana Buddhist temple, one of the monasteries with a new stream in Surabaya. This monastery is still building and have some problems such as to visualize its room to be seen as Buddhayana streams in Dhammasala room, air quality issues that must be free from over-smoke needed, acoustic that has to be soundproof from other noises.Design method used is property d. school paris that describes every design process : inspiration, ideation, test, dan implementation. This design concept using “Naturalize Soul” approaching Buddha teaching, Zen, which teach “emptiness” in soul. This emptiness applied with simplicity and not distrubing any activities going. This design provides design which Buddism values applied to its interior through symbols valued to Buddhayana, air quality needed to be smoke free using exhaust fan and providing air conditioner as subtitute of air that vacumed by exhaust, also solving acoustic conditions using soundproof materials.